Educational Service Quality as a Mediator Between Principal Leadership and Teacher Job Satisfaction - Eli Karyati; Aan Komariah; Djam’an Satori; Sururi Sururi; Supiani Supiani (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine the mediating role of educational service quality in the relationship between principal leadership and teacher job satisfaction in disadvantaged educational settings. A quantitative explanatory research design was employed involving 310 junior high school teachers from rural area. Data were collected using a structured questionnaire measuring principal leadership, educational service quality, and teacher job satisfaction. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect effects among the constructs. The results revealed that principal leadership had significant positive effects on both teacher job satisfaction and educational service quality. Educational service quality also significantly enhanced teacher job satisfaction. Furthermore, educational service quality partially mediated the relationship between principal leadership and teacher job satisfaction, indicating that effective school leadership improves teacher satisfaction both directly and indirectly by fostering higher-quality educational services. These findings highlight the importance of service-oriented leadership practices in strengthening teacher well-being and enhancing school performance in disadvantaged educational settings. The study contributes to the educational leadership literature by demonstrating the mediating mechanism through which principal leadership influences teacher job satisfaction and provides empirical evidence to support leadership development strategies aimed at improving educational service quality and sustainable school effectiveness in rural area.